IMPROVING BIO-OIL QUALITY VIA CO-PYROLYSIS EMPTY FRUIT BUNCHES AND POLYPROPILEN PLASTIC WASTE - Sunarno Sunarno; Alfi Randi; Panca Setia Utama; Silvia Reni Yenti; Wisrayetti Wisrayetti; Doni Rahmat Wicakso (Universitas Lambung Mangkurat, 2021)
The current consumption of fuel oil, especially gasoline and diesel oil, is increasing. Along with the decline in production, national oil production activities encourage efforts to find alternative fuels as a substitute for oil-based energy supplies. Bio-oil is an environmentally friendly alternative fuel for diesel that can be used as fuel. In this study, the raw materials were palm oil empty bunches and polypropylene plastic waste. The purpose of this study was to determine the effect of the ratio of raw material for oil palm empty fruit bunches and polypropylene, the effect of co-pyrolysis temperature on the yield of bio-oil and determine the characteristics of the resulting bio-oil. This study used the variable ratio of oil palm empty fruit bunches and polypropylene (100:0, 80:20, 70:30 and 60:40) and co-pyrolysis temperature (400, 450, 500 and 550 °C). The results showed that the highest yield of bio-oil was obtained, namely 41.6% with a ratio of EFB: PP (80:20) at temperature of 450 °C. The characterization of the product obtained was density of 0.891 g/ml, viscosity of 4.18 cSt, pH of 3.38 and calorific value of 43.2 MJ/kg.